2018
DOI: 10.1021/acs.biomac.8b00517
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Applications of Cellulose Ethers and Cellulose Ether Esters

Abstract: Cellulose ethers have proven to be highly useful natural-based polymers, finding application in areas including food, personal care products, oil field chemicals, construction, paper, adhesives, and textiles. They have particular value in pharmaceutical applications due to characteristics including high glass transition temperatures, high chemical and photochemical stability, solubility, limited crystallinity, hydrogen bonding capability, and low toxicity. With regard to toxicity, cellulose ethers have essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(124 citation statements)
references
References 237 publications
0
115
0
2
Order By: Relevance
“…[2] Among the cellulose derivatives, methyl cellulose (MC) has extensively been used for applications related to foods, detergents, paints, adhesives, cosmetics, safety, and gels. [3][4][5] Therein, MC acts as an emulsifier, viscosity controller, and mechanical adjuvant for composite systems. [6] It has been shown that 2.49 wt% of MC having molecular weight of 310 kDa and a degree of substitution of 1.8 display lower critical solution temperature (LCST) at 29 ± 2 o C, below which Newtonian flow is observed and above which non-Newtonian flow and increased viscosity emerge.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Among the cellulose derivatives, methyl cellulose (MC) has extensively been used for applications related to foods, detergents, paints, adhesives, cosmetics, safety, and gels. [3][4][5] Therein, MC acts as an emulsifier, viscosity controller, and mechanical adjuvant for composite systems. [6] It has been shown that 2.49 wt% of MC having molecular weight of 310 kDa and a degree of substitution of 1.8 display lower critical solution temperature (LCST) at 29 ± 2 o C, below which Newtonian flow is observed and above which non-Newtonian flow and increased viscosity emerge.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of cellulose chemistry, many derivatives have been developed and some are even produced in industrial scale. [1] However, introduction of sophisticated functional substituents requires advanced reaction pathways. It was studied to generate artificially branched derivatives [2] that can be achieved…”
Section: Introductionmentioning
confidence: 99%
“…21 The industrial production of cellulose derivatives, such as cellulose esters and ethers, resulted in dramatic changes in the material properties. 32 Limited control over the degree of modification prevents detailed structure-property correlations to be established and generates unreproducible results. Synthetic well-defined polysaccharides allowed for definitive correlations between the increased flexibility of the single chain and the reduced aggregation, precipitation, and regular packing upon drying.…”
Section: Polysaccharide Materialsmentioning
confidence: 99%